AN UP-TO-DATE FOREIGN LANGUAGE COURSEBOOK: FROM PAPER TO ELECTRONIC VERSION - O. A. Kravtsova; D. N. Novikov (Vestnik MGIMO-Universiteta)
The article attempts to articulate the conceptual characteristics of an up-to-date tertiary-level foreign language coursebook. In order to meet the requirements of modern national educational standards and be in line with the aims of foreign language teaching, a new generation coursebook, whether printed or electronic, is to be based on a set of such general didactic principles as competency-based approach, interdisciplinary approach, multilevel approach, modularity, and proximal development as well as such specific language teaching principles as authenticity, up-to-dateness, informativeness, and functionality. The authors substantiate the need for an integrative approach to developing an innovative coursebook, which consists in blending a printed and an electronic version, thus allowing for a more optimal organisation of the teaching-learning process due to a more rational proportion between classroom and self-study activities. The effective organisation of the process, in its turn, is instrumental in achieving the aims and goals of foreign language teaching. New generation coursebooks can be used not only to organise independent and self-study activities of full-time students of higher education, but also to provide a basis for various forms of distant learning, which will enable up-country students to receive high-quality (language) education.